Impact of Artificial Intelligence (AI) on Television - Konstantinova, Maria (Проблеми на постмодерността, 2025)
In this report, I examine the impact of artificial intelligence on journalism and television in particular, as well as the main positive and negative aspects of the introduction and implementation of AI technology in the media. The purpose of the report is to trace the first steps in the use of artificial intelligence in the media, the strengths and weaknesses of the new technology, and the concerns of people that artificial intelligence will replace them in the profession. When choosing the methodology for conducting the research, the nature of the set goal was taken into account, adhering to the principles of high ethics and efficiency of quantitative and qualitative indicators and criteria. The results highlight various studies that indicate the audience's opinion of the use of artificial intelligence in the media and take into account the opinions of the world's information agencies for the preparation of rules for the use of artificial intelligence in the media. Examples of the use of artificial intelligence in Bulgarian television are also indicated here. The discussion raises the question of copyright and the regulation of the use of artificial intelligence, an issue that has been seriously debated in the European institutions, which at the end of last year reached an agreement on the rules governing the use of AI. In conclusion, it is clear that despite the possibilities of processing and generating information from artificial intelligence, it is far from displacing journalists in their work, because its refinement has not yet reached the point where it has emotions and is creatively directed. All this shows that the limits of artificial intelligence will be set by natural intelligence in the face of people, and it only depends on us how far it will reach in its development and implementation in various fields.